Case Report: Aseptic spondylodiscitis revealing non-radiographic axial spondyloarthritis associated with Crohn's disease - Jomaa, Olfa; Abid, Hayfa; Brahem, Mouna; Neifar, Olfa; Ardhaoui, Mahbouba; Sarraj, Rihab; Younes, Mohamed (Frontiers in Musculoskeletal Disorders, 2025)
Aseptic spondylodiscitis (SD) is a rare complication of axial spondyloarthritis (AS) that can develop during the course of the disease, often asymptomatically. Magnetic resonance imaging (MRI) is the gold standard for diagnosing SD, but due to its rarity, the condition is frequently misdiagnosed. We report the case of a 60-year-old male who presented with back pain and elevated erythrocyte sedimentation rate (ESR) and C-reactive protein (CRP) levels. MRI of the dorsolumbar spine revealed SD from the D6 to D8 vertebrae. An infectious workup was negative. During hospitalization, the patient developed acute abdominal pain, cessation of bowel movements, and gas retention. Abdominal CT revealed ileitis, prompting a colonoscopy, which confirmed Crohn's disease (CD) through histopathological analysis. Pelvic MRI also showed sacroiliitis. The diagnosis of aseptic SD revealing non-radiographic AS associated with CD was made according to the ASAS 2009 criteria, and the patient was treated with sulfasalazine, showing favorable improvement. Only a few cases of SD in patients with AS and inflammatory bowel disease (IBD) have been reported. This case underscores that SD can be the initial clinical manifestation of non-radiographic AS associated with CD. Although challenging to recognize, this condition may present with unpredictable and varied clinical symptoms, requiring a comprehensive diagnostic approach.